Physicochemical, microbiological, and sensory properties of healthy juices containing aloe vera gel and probiotics and their antidiabetic effects on albino rats - Moselhy, Sara Naiim; Al-Nashwi, Ahmed Aladdin; Raya-Álvarez, Enrique; Abu Zaid, Fouad Omar; Shalaby, Hanan Said Tawfik; El-Khadragy, Manal F.; Shahein, Magdy Ramadan; Hafiz, Amin A.; Aljehani, Abeer A.; Agil, Ahmad; Elmahallawy, Ehab Kotb (Frontiers in Nutrition, 2024)
The consumption of fruit and vegetable juices is widely recognized as a healthy choice across all age groups. Orange, carrot, and aloe vera are globally renowned for their functional properties and health benefits. In this study, we investigated the potential incorporation of Aloe vera gel into blended orange and carrot juices, besides evaluation of the resulting mixed probiotic juices (chemical, microbiological, and sensory aspects) during a 14-day storage period at refrigerator temperature. The chemical composition and phytochemical structure of Aloe vera gel was examined, followed by an assessment of the biological effects of these healthy juices on diabetic albino rats. The results indicated improvements in total soluble solids, reducing sugars, and total sugars with increasing storage duration. Furthermore, the study demonstrated that incorporating Aloe vera into the natural mixed juices enhanced their phytochemical quality. The treatment supplemented with aloe vera gel gave the highest total content of phenolic and flavonoid substances, which were 310 mg of GAE/ 100 g and 175 mg of quercetin/ 100 g, respectively. Probiotic strains (Bifidobacterium animalis subsp lactis Bb12, Lactiplantibacillus plantarum 299V, and Lactobacillus acidophilus L10) exhibited good viable cell counts in orange and mixed orange and carrot probiotics juices with viable counts of 7.42–8.07 log CFU/mL. Regarding sensory attributes, the study found that increasing the ratio of orange juice improved the taste, while increasing the ratio of carrot juice enhanced the color in juice mixtures. Incorporation of aloe vera into mixed natural juices also enhanced the reduction of blood glucose, triglyceride, cholesterol, LDL, creatinine, ALT, AST, and urea levels, while increased total protein and HDL levels in diabetic rats. Based on these findings, oranges, carrots, and aloe vera offer the potential to produce new, flavorful, nutritious, and appealing juices. Moreover, this study determined that a functional juice with favorable sensory properties can be created by blending 75% orange juice, 20% carrot juice, and 5% aloe vera gel. Additionally, Aloe vera demonstrates greater efficacy as an anti-diabetic agent in rats. Further research is suggested to explore the potential advantages of aloe vera gel and probiotic juices in mitigating diabetes and other metabolic syndromes.